The Role and Significance of EU Funds for the Republic of Croatia - Marija Tolušić; Nikolina Koporčić; Zdravko Tolušić (Ekonomski Vjesnik, 2013)
The Republic of Croatia was granted the official candidate country status for the membership in the European Union on 18 June 2004. Thus it gained the opportunity to use pre-accession funds aimed at helping the candidates to bring their institutions and standards in line with the EU legislation. Nevertheless, full EU membership will bring further major changes. The paper presents a survey conducted on 106 respondents, which intended to establish how familiar people are with the topic of project management, EU funds and possibilities afforded by those funds. The problems currently noticeable in Croatia arise from high unemployment, lack of highly skilled personnel and their high turnover, low level of information and experience, coupled with risk aversion and fear of project failure. The consequence is less than full preparedness for taking advantage of all the available funding. Following full EU membership Croatia will gain access to the Structural Funds and the Cohesion Fund which provide numerous opportunities for financing of infrastructural projects such as roads, railways and waterways, social development, retraining for the unemployed and creating new jobs, youth mobility, promoting diversity, environment protection and alternative energy sources. This requires a fair number of well-informed and trained people, capable of writing a good project and of implementing it in line with EU procedures. It is therefore imperative for the government and public institutions to invest into training of both the general public and potential future experts.